Superplume mantle tracked isotopically the length of Africa from the Indian Ocean to the Red Sea - O'Connor, John; Jokat, Wilfried; Regelous, Marcel; Kuiper, Klaudia; Miggins, Dan P.; Koppers, Anthony A P (Nature Communications, 2019)
Seismological findings show a complex scenario of plume upwellings from a deep thermo-chemical anomaly (superplume) beneath the East African Rift System (EARS). It is unclear if these geophysical observations represent a true picture of the superplume and its influence on magmatism along the EARS. Thus, it is essential to find a geochemical tracer to establish where upwellings are connected to the deep-seated thermo-chemical anomaly. Here we identify a unique non-volatile superplume isotopic signature ('C') in the youngest (after 10 Ma) phase of widespread EARS rift-related magmatism where it extends into the Indian Ocean and the Red Sea. This is the first sound evidence that the superplume influences the EARS far from the low seismic velocities in the magma-rich northern half. Our finding shows for the first time that superplume mantle exists beneath the rift the length of Africa from the Red Sea to the Indian Ocean offshore southern Mozambique.